Translation Procedures of the Subtitle of the Ant-Man Movie: A Pragmatic Study - Gading, Arya; Baharuddin; Lalu Jaswadi Putera; Arifuddin (Journal of Authentic Research, 2025)
This study investigates translation procedures and pragmatic implications in the Indonesian subtitles of the film Ant-Man. Using Newmark’s translation procedure framework and supported by the pragmatic theories of Austin et al., Searle, and Cutting, this study aims to identify the types of translation procedures applied, determine the most dominant procedures, and analyze how they preserve meaning in context. Employing descriptive qualitative methods with content analysis, the dialogue data were coded and then interpreted through Newmark’s translation procedure theory, Austin and Searle’s speech acts theory, and Cutting’s context classification theory. 114 subtitle sentences were examined, of which 75 were categorized as pragmatic utterances. The findings present that ten out of eighteen procedures were identified, with Modulation being the most dominant (42.11%), followed by Couplets/Triplets (22.81%) and Literal Translation (13.16%). Pragmatic analysis indicates that procedures such as Modulation, Couplets, Functional Equivalent, Cultural Equivalent, and Synonymy have played an important role in maintaining humor, sarcasm, idiomatic expressions, and cultural nuances ensuring that the communicative intent is conveyed effectively to the Indonesian audience. This study contribute to bridging the analysis of translation procedures and pragmatic interpretation in audiovisual translation in terms of variations in equivalent meanings based on context. Furthermore, practically, the findings of this study can be useful for translators or subtitlers to pay more attention to the equivalence of meaning, not just based on the literal meaning, to avoid audience confusion.